Athletes' expectations about physiotherapy in sports injury rehabilitation in greater Accra region - Jonathan Quartey; Selorm Afidemenyo; Samuel Koranteng Kwakye (World Scientific Publishing, 2019)
Background: Physiotherapists play a key role in sports injury rehabilitation within the sports healthcare team. A strong athlete-physiotherapist relationship is necessary for effective treatment and shaping of athletes' expectations of injury rehabilitation. Hence, it is necessary to factor the injured athletes' expectations in structuring a rehabilitation program. Objective: The aim of this study was to determine athletes' expectations about physiotherapy in sports injury rehabilitation. Methods: We performed a cross-sectional survey in which data was collected using the expectation about athletic training (EAAT) questionnaire from 120 recruited athletes of different sporting disciplines. Percentages, means and standard deviations of the expectation scores were computed. Associations between socio-demographic characteristics and athletes' expectations of physiotherapy in sports injury rehabilitation were analyzed with the chi-square test. Differences between the athletes' expectations of physiotherapy and demographic characteristics were also analyzed with Kruskal-Wallis and Mann-Whitney tests. Results: The study revealed that there was no significant difference (p>0.05) between gender, injury type, physiotherapy experience and mental skills experience and the athletes' expectations. There was a significant difference (p<0.05) between competition level and athletes' expectations. Conclusion: It was concluded that athletes in the Greater Accra Region have high expectations of physiotherapy in injury rehabilitation; thus sports physiotherapists would need to enhance their communication with athletes which may also help them better understand the risks, benefits, timeline and rehabilitation approach.